Factors affecting the quality of training and development of employees working at small and medium enterprises belonging to the Ho Chi Minh city enterprise association - Ngo, Phan Vu Gia Binh (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
The article focuses on researching "Factors affecting the quality of training and development of employees working at small and medium enterprises under the Ho Chi Minh City Business Association". By collecting, synthesizing and analyzing data from 350 survey forms of employees working at small and medium enterprises, the author proposed 5 factors affecting the quality of training and development of employees including: Development orientation of employees at the enterprise; Working environment conditions; Professional and skill requirements of the job position; Socioeconomic development policies of the Government and Labor migration trends. Through the research, businesses will have more information and assessments from the perspective of employees, thereby being able to make adjustments and develop policies related to training and development policies to suit the actual situation and help maximize efficiency at the enterprise.